STYLISTIC STUDY: WASIAT’S RENUNGAN MASA PENGALAMAN BARU - Muhamad Ahyar Rasidi Rasidi; Ernaliana; Adamu Abubakar Muhammad (Yayasan Cendekia Citra Gemilang, 2025)
This study aims to analyze the typical language style of Islamic boarding schools and the meaning of the content of the poem Wasiat Renungan Masa Pengalaman Baru (WRMPB) TGKH. Zainuddin Abdul Majid. This study is a text analysis study that was analyzed using content analysis. The focus of this study is on typical Arabic words/phrases. Arabic words/phrases are considered more effective in conveying the message. The study’s results found several things, including: 1) The form of typical Islamic boarding school language style is focused on utilizing Bradford’s theory, Arabic vocabulary, and Arabic phrases. Bradford’s theory is analyzed using contextual stylistics, including syllable repetition, matrix patterns, repeated rhymes, assonance, and alliteration. 2) The meaning of the typical Islamic boarding school style is analyzed using Bradford’s theory using textual stylistics, which includes: elements of motif, metalingual, reference, and conative. The limitations and suggestions of this study for subsequent researchers are that the interpretation of poetry using Arabic does not use more comprehensive Nahwu and Shorof rules due to limited knowledge.